Konsep dan Etos Ilmu dalam Ensiklopedi Al-Qur'an Karya Dawam Rahardjo - Zakiy, Ahmad (ANWARUL, 2024)
The fact of the decline of the Muslim world in terms of intellectual level has been discussed in many places. The response to these challenges is very diverse. One response that is considered relevant is to bring back the spirit of the Qur'an to revive the tradition of knowledge. This research aims to explore the concept and ethos of knowledge in the book Encyclopaedia Al-Qur'an by Dawan Rahardjo. This type of research is library research using descriptive-analytical method. The results of this study are, in his introduction, Dawam explains the ethos of science in the Islamic world, where the concept of knowledge sourced from the Qur'an and hadith became the driving force of Islamic society in the past in creating an advanced civilisation. Regarding the interpretation of the Qur'an, Dawam raises all vocabulary that contains elements of 'knowledge' which is not limited to the word 'ilm and its various derivations, but other vocabulary such as fahhama, 'aqala, bashir, faqiha, khabara, albab, and so on in revealing the meaning of 'knowledge' in the Qur'an. On the other hand, Dawam raises one sample surah, QS. al-An'am to show that the Qur'an encourages its people to act in a rational way and has functional value. Finally, Dawam concludes that although the Qur'an contains theological aspects as a religious teaching, as a teaching of life, the Qur'an also contains practical aspects of the spirit to be knowledgeable, act rationally, and also create a scientific civilisation.